Percutaneous mechanical thrombectomy device assisted TIPS recanalization: a feasibility study. (September 2022) - Thurner, Annette; Augustin, Anne Marie; Götze, Oliver; Bley, Thorsten A; Kickuth, Ralph
Background: Despite improved shunt patency, transjugular intrahepatic portosystemic shunt (TIPS) occlusion remains a serious complication, and effective debulking of the existing tract is needed to restore sufficient blood flow. Purpose: To evaluate the technical and clinical success of percutaneous mechanical thrombectomy in restoring patency of acutely and chronically thrombosed covered TIPS using the Aspirex®S and Rotarex®S system. Material and Methods: We evaluated mechanical thrombectomy-assisted revisions in five patients between January 2012 and April 2021. Two patients had to be revised twice due to recurrent occlusion. We designated thrombosis within 10 days after shunt creation or revision as acute. Insidious deterioration of portal hypertension related symptoms for at least 6–8 weeks was recorded in chronic cases. We treated four acute and three chronic occlusions. After transjugular lesion crossing, we performed two mechanical thrombectomy device passages. If indicated, balloon dilatation, covered stent placement, or variceal embolization were added. Results: The technical success rate was 100%. No procedure-related complications occurred. In one patient with acute decompensation of Budd–Chiari syndrome and acute-on-chronic liver failure, early re-thrombosis occurred twice with patency intervals of up to eight days. In contrast, stable patency was achieved in the other four patients with documented patency intervals of at least five months and improvement of portal hypertension-related symptoms, resulting in a patient based clinical success rate of 80%. Conclusion: In five patients, percutaneous mechanical thrombectomy assisted TIPS recanalization of four acute and three chronic occlusions proved to be technically feasible and safe with a high clinical success rate.